Determinants of Stunting in Majalaya, Bandung - Fauziah, Diah Adni; Nuraeni, Widia (Corespub, 2025)
The children period is known as the golden age of development because at this stage there is an acceleration of physical and mental growth. However, at the same time, children are also an age group that is very vulnerable to various health problems, one of which is prone to nutritional disorders, especially nutritional problems in children, such as stunting. This study aims to look at the determinants of stunting in Majalaya, Bandung using a case control study design. The selection of respondents used random sampling techniques. The case group consists of 15 children aged 24 to 59 months who have stunted status in Padaulun Village in March 2025. The control group is 45 children aged 24 to 59 months who are not stunted in Padaulun Village in March 2025. Data were analyzed using logistic regression tests. The results of the study were obtained from the variables of Mother's education (p=0.017; OR=11; 95%CI 1.048-115.510) and feeding pattern (p=0.002; OR=6.76; 95%CI 1,820-25,174) had an effect on the incidence of stunting in children, while the variables of maternal age and maternal occupation had no effect on the incidence of stunting in children. The results of the multivariate analysis showed that only feeding pattern was the most significant to increase the incidence of stunting. Regular education is needed about the right feeding pattern for mothers who have children so that the risk of stunting can be minimized.